Objectifying Anxieties: Scientific Ideologies in Bram Stoker’s Dracula and The Lair of the White Worm - Long Hoeveler, Diane (Romanticism on the Net, 2006)
AbstractScientific ideologies swirl throughout Stoker’s two most gothic novels, Dracula (1897) and The Lair of the White Worm (1911), and this essay will address those ideologies as literary manifestations of just some of the “weird science” that was permeating late-nineteenth- and early-twentieth-century Europe. Specifically, the essay examines racial theories, physiognomy, criminology, brain science, and sexology as they appear in Stoker’s two novels. Stoker owned a copy Johann Caspar Lavater’s five-volume edition of Essays on Physiognomy (1789), and declared himself to be a “believer of the science” of physiognomy. The second major “weird science” infecting the gothic works of Stoker is the new field of criminology, or the bourgeois attempt to codify, control, and exterminate criminal elements in the human population. Stoker drew on both Havelock Ellis’s The Criminal, published in 1890, and the Italian Cesare Lombroso’s work, Uomo Delinquente (1876), a book that was available to Stoker in a two volume French translation published as L’Homme Criminel (1895). Stoker derived a number of his passages about the workings of the brain from the theories of the well-known professor of physiology, W. B. Carpenter, founder of the notion of “unconscious cerebration,” a concept developed in his book Principles of Mental Physiology (1874). Finally, Richard von Krafft-Ebing published his pioneering text on sexuality in 1886, Psychopathia Sexualis, with Special Reference to Contrary Sexual Instinct: A Medico-Legal Study, and invented the scientific study of sex. Of a piece with criminology, sexology attempted to categorize and medicalize human behaviors in such a way that all would become clear to the informed and enlightened bourgeois consciousness. As another weirdly scientific effort to “discipline and punish,” sexology sought to transform crime into perversion, and the man or woman suffering from vampiric tendencies became just another case study of sexual deviancy.